Innovative Design of Marketing Ecosystems - А. I. Vasiliev; I. А. Brusakova (Управленческие науки)
This study is devoted to the issues of ecosystems and the ecosystem approach. The formation and use of marketing ecosystems can simplify both the processes of transformation of technological patterns and the interaction of different types of business models of enterprises. A separate focus is on marketing ecosystems as one of the important innovations of Industry 5.0. The transition from Industry 4.0 to Industry 5.0 is accompanied by the creation of the necessary software and algorithmic base of quantum computing, introduction of technologies for visualisation of management decisions, development of neuromorphic models of enterprise architecture, digital twins of business processes.The purpose of the study is to develop approaches to designing a marketing ecosystem within the framework of Industry 5.0 and Industry 4.0, which is necessary for building effective interactions between innovative enterprises of different business spheres. The article considers the stages of innovative design of new marketing ecosystems, the result of which is the end-to-end integration of information resources of their member enterprises, which is necessary for the consolidation and synchronisation of structured and unstructured data on different business models of companies and the organisation of predictive analytics mechanisms. In the course of the work, the method of scientific analysis of literature on the research problem was applied, and the empirical experience of the authors of the article was used. The results of the study will be useful to all managers of innovative companies as well as the heads and employees of marketing departments of these companies.